The Influence of Return on Assets, Current Ratio and Debt to Asset Ratio on Financial Distress in Consumption Goods Industry Sector Companies Listed on The Indonesia Stock Exchange in 2017-2021 - Shoeibatul Aslamiah; Subur Karyatun; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2023)
The purpose of this study was to analyze the impact of Return On Assets (ROA), Current Ratio (CR), and Debt to Assets Ratio (DAR) on financial distress for companies in the consumer goods industry sector during the 2017-2021 period. The population in this study were companies in the consumer goods industry sector which were listed on the Indonesia Stock Exchange from 2017 to 2021. Sampling was carried out by purposive sampling based on the criteria, a sample of 20 companies was obtained. The data source used is secondary data with the documentation method. The analytical method used is descriptive analysis and logistic regression with a significance level of 0.05 using the IBM SPSS 25 program. The results of this study indicate that return on assets (ROA) and debt to asset ratio (DAR) have a positive and significant effect on financial distress. Current ratio (CR) has no effect on financial distress. Through the results of this study it is hoped that it can help company managers in consumer goods industry sector companies to continue to improve effective and efficient financial ratios in order to avoid financial distress.